Cultural border crossings in the UAE : improving transitions from high school to higher education - Hatherley-Greene, Peter (Curtin University, 2012)
Over the course of one academic year, I documented the experiences of new first-year male Emirati students at a college of higher education in the United Arab Emirates. Using Giroux’s metaphor of a cultural border crossing, I described and attempted to explain the gamut of transition experiences as young male Emirati school-leavers move from their pre-dominantly Arabic life-world associated with their families and schooling to the pre-dominantly Western culture found in higher education. I additionally investigated factors associated with both students and faculty that hinder and/or enhance student learning, and I assessed best practices in the college administrative and academic areas which appeared to facilitate smoother cultural border crossing experiences for new students. I adopted a multi-paradigmatic research design that drew methods and quality standards from multiple paradigms to create a methodology that enabled an artful, critical and interpretive exploration of complexity supplemented by a descriptive analysis of general social patterns.The latter was achieved by survey research methods and the former using observation, case studies, interviews, journals, student narratives, and focus groups. A Border Crossing Index broadly correlated with the four placement levels of students in Foundations with the result that those students placed in the lower levels were much more likely to leave college and seek full-time employment within the first semester – 66% of the new students left college during the year. Suffering from the effects of neo-indigeneity and a disempowering ‘rentier effect’, I identified almost twice as many factors that appeared to hinder student learning as enhance it. Mainly Western teachers who developed a classroom culture based on ‘warm demandingness’ and rapport-building appeared to have the most positive impact upon the students. The development of students’ soft-skills in a new College Preparation and Readiness (CPR) program was assessed using a Mental Toughness Questionnaire which surprisingly produced lower post-test scores, indicating possibly greater self-awareness and honesty.I offered a series of suggestions from the macro societal level such as more engaged parenting, addressing a potentially devastating ‘rentier effect’, and improving the quality of education especially in the government high schools to smaller ‘tipping point’ changes at the micro college and classroom level. A key emerging question asks - whose interests are being served (or not) by compelling first-language students to cross cultural borders into higher education colleges and asking them to study using the dominant and hegemonic second-language of English?